2018
DOI: 10.4048/jbc.2018.21.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Suppresses Fibronectin Expression through Inhibition of c-Jun Phosphorylation in Breast Cancer Cells

Abstract: PurposeThe exact mechanism regulating fibronectin (FN) expression in breast cancer cells has not been fully elucidated. In this study, we investigated the pharmacological mechanism of berberine (BBR) with respect to FN expression in triple-negative breast cancer (TNBC) cells.MethodsThe clinical significance of FN mRNA expression was analyzed using the Kaplan-Meier plotter database (http://kmplot.com/breast). FN mRNA and protein expression levels were analyzed by real-time polymerase chain reaction and western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…For the individual cancer types, the top ovarian cancer cell selective inhibitor was fostamatinib [35] (IC 50 = 6.24 ± 4.06 μM; SI >100), a Syk kinase inhibitor (Supplementary Figure 8 A - D and Table 3). The top placental cancer line inhibitor was berberine [36], [37] (IC 50 = 4.41 ± 0.662 μM; SI >100), an anti-parasitic alkaloid targeting Complex I of the mitochondrial respiratory chain and AP-1 machinery (Supplementary Figure 8 E - H and Table 3). The cervical cancer selective inhibitory compounds found in our study were also active for the ovarian cancer cells.
Figure 2Chemotherapeutic diversity in cell line killing.
…”
Section: Resultsmentioning
confidence: 99%
“…For the individual cancer types, the top ovarian cancer cell selective inhibitor was fostamatinib [35] (IC 50 = 6.24 ± 4.06 μM; SI >100), a Syk kinase inhibitor (Supplementary Figure 8 A - D and Table 3). The top placental cancer line inhibitor was berberine [36], [37] (IC 50 = 4.41 ± 0.662 μM; SI >100), an anti-parasitic alkaloid targeting Complex I of the mitochondrial respiratory chain and AP-1 machinery (Supplementary Figure 8 E - H and Table 3). The cervical cancer selective inhibitory compounds found in our study were also active for the ovarian cancer cells.
Figure 2Chemotherapeutic diversity in cell line killing.
…”
Section: Resultsmentioning
confidence: 99%
“…BBR is known to be a low-toxicity and safe agent and was reported to have multiple biological functions, including antimicrobial, anti-inflammatory, and antitumor effects [4,5,6,7,8,9,10,11,12,13]. Treatment with 13-EBR, a BBR analog that is substituted at C-13 by alkyl groups, was reported to have anti-inflammatory effects [16,17]; however, the role of this molecule in tumor suppression was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine (BBR) is an isoquinoline alkaloid that is isolated from Cotridis rhizoma and has multiple biological activities, such as antimicrobial, anti-inflammatory, and antitumor effects [4,5,6,7]. In particular, the anticancer effects of BBR on breast cancer cells were reported; BBR induces breast cancer cell apoptosis via the activation of the apoptotic signaling pathway [8,9], the inhibition of proliferation and migration [10], the suppression of cell motility through the downregulation of related molecules [11,12], and the enhancement of chemosensitivity, which induces apoptosis [13]. Recently, it was reported that 13-alkyl-substituted berberines showed better antimicrobial activity against certain bacterial species and cytotoxic activity against human cancer cell lines than BBR [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor-suppressor protein TP53 is a transcription factor that regulates anti-carcinogenesis programs associated with apoptosis, cell cycle arrest, and DNA repair in genotoxic and not-genotoxic cellular injuries (32,33). In recent studies, we reported that the level of fibronectin expression is associated with the status and expression of TP53 in breast cancer cells (34,35). Wu et al reported that Slug is transcriptionally induced by TP53 and then escapes from apoptosis by repressing the TP53-mediated transcription of Puma (36).…”
Section: Discussionmentioning
confidence: 99%